Production of abrasive apricot kernel shell powder/boron nitride/polyester composites for cleaning of paint and corrosion on metal surfaces - Bahce, Erkan; Demirel, Maruf H.; Koytepe, Suleyman; Seckin, Turgay (Wiley, 2020)
In this study, the synthesis and characterization of abrasive polyester composite discs reinforced with apricot kernel shell (AKS) particles and hexagonal boron nitride (BN) were carried out as an alternative to the methods used to remove the surface corrosion from metallic surfaces. Polyester composites were obtained by unsaturated polyester resin as a matrix and AKSs (1%, 3%, 5% and 10% weight ratio) with 200 mesh and 1% BN as reinforcements. Kernel shells as a source of cellulose were used for increasing mechanical stability of abrasive composite discs. The structure and chemical properties of the obtained composites were characterized by Fourier transform infrared spectrometer, X-ray spectrophotometer and SEM analysis. Their thermal properties were determined by differential thermal analysis, thermogravimetric analysis and differential scanning calorimetry. The synthesized polyester composites were molded into cylindrical discs and the corrosion and paint layer abrasive properties of these discs on different corroded metal surfaces were investigated. The hardness of the prepared abrasive polyester composites were also measured as mechanical properties. The hardness values of prepared abrasive discs were determined as 21.9, 22.1, 23.4, 24.5 and 25.9 +/- 0.1 for pure PE, 1%, 3%, 5% and 10% composites, respectively. In addition, the cleaning ability of the abrasive composites on the metal surface was determined by measuring the surface roughness and the amount of peeling. As a result, it has been determined that the most suitable optimum conditions are achieved with a contribution of 10% AKS particles reinforced composite structure considering the features such as cleaned surface roughness, cleaning suitability and composite abrasion.
Keywords: abrasive material; apricot kernel shells; BN; polyester composite